Shoulder impingement in tennis players - Rosenkranz, M. (1997)
From September 1994 to June 1996, 47 tennis players aged 25 to 67 underwent shoulder arthroscopy due to shoulder impingement syndrome. In all cases, conservative treatment was unsuccessful. In addition to a detailed physical examination, all patients were surveyed by static and dynamic shoulder sonography. The patients were assigned to one of four groups, with the aim of comparing sonographical and arthroscopical results. The overall accuracy of sonography regarding glenoid labral damage was only 51%. There were great individual variations in ultrasound evaluation of shoulder instability. The results of the study show that shoulder sonography can be an additional method for investigating the different causes of shoulder pain in tennis players, but sufficient documentation of labrum defects by shoulder sonography is not possible. Shoulder arthroscopy enables identification of intra-articular and sub-acromial damage. Based on an exact diagnosis, tennis players can be guided to the right therapy and rehabilitation programme.